THE EFFECT OF GREEN ACCOUNTING AND CSR IMPLEMENTATION ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Saputra, Muh. Hatta Cahaya; Ridwan, Muhtadi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Knowing the rapid progress of the business will easily increase the activity of the business, from different sources in this world, especially in the income. By performing these activities, mining companies contribute to positive and negative environmental conditions and social inequality for people living around the industry. This study used a quantitative approach by collecting secondary data. This study used purposive sampling. The data analysis technique used is multiple linear analysis and Moderated Analysis Regression (MRA) with the SPSS version 23 application. The samples used in this study are mining sector companies listed on the Indonesia Stock Exchange during 2019-2022. The results of this study show that green accounting information affects enterprise value and that corporate social responsibility has no effect on enterprise value. The findings of this study also suggest that good corporate governance does not moderate the impact of green accounting and corporate social responsibility disclosure on firm value. The data analysis method used is multiple linear analysis and moderate regression analysis (MRA) with the SPSS version 23 application. The sample used in this study consists of mining companies listed on the Indonesian stock exchange at the time of year 2019-2 The results of this study show that green accounting information affects enterprise value, and corporate social responsibility has no effect on enterprise value. The findings of this study also suggest that good corporate governance does not moderate the impact of green accounting and corporate social responsibility disclosure on firm value.